Efektifitas Modul Peningkatan Kesehatan Reproduksi Terhadap Kesadaran Diri siswa SMPN se Kodya Malang - Ch. Erghiezha Ninuk Indrati K (Universitas Kanjuruhan Malang, 2016)
Reproductive health is as a health condition not free ill disabilities,but good mental health or social helth be releted to with system function and process reproduction with self awareness. This study is pre experiment with one group pre tests post tests design. The subject of research 53 junior high school students throughout of Malang with the selection of subjects designated by counseling teachers retieving data using research instrument using a scale of self awareness of reproductive health.Treatment using modul increase self awareness of reproductive health. The finding of this study revearls is value t test 3.031 with sig .003. The average self awareness of reproductive health before 128.4151 and after treatment 178.1887 is different or there different self awareness junior hight school before and after treatment. Keyword: Reproductive Health, Self Awareness